P056 REducing Sleep Apnoea for the PrEvention of Dementia (REShAPED): The protocol of a multi-site feasibility randomised controlled trial. (9th November 2022) - Hoyos, C; Phillips, C; Yaffe, K; Martins, R; Marshall, N; Lagopoulos, J; Jackson, M; Mowszowski, L; Grunstein, R; Naismith, S
Abstract: Background: Obstructive sleep apnoea (OSA) is estimated to occur in up to 70% of older adults. There is accumulating evidence linking OSA with increased risk of cognitive decline and dementia. Here, we present the protocol for a pilot multi-site randomised controlled, parallel open-label trial which will evaluate the feasibility for a full-scale trial investigating the effects of treating OSA on cognitive decline in older adults at risk for dementia with OSA within memory clinic settings. Methods: We will randomise 180 older adults to either the intervention group or to the control group for 2 years. Inclusion criteria include: 50-75 years; mild-severe OSA (defined average ODI≥10 with 3% oxygen desaturation determined by wrist oximetry over two nights); and subjective cognitive complaints or mild cognitive impairment. The treatment intervention arm intends to achieve an optimal treatment response based on reducing hypoxic burden with either CPAP, mandibular advancement splint, positional therapy, or oxygen therapy. Furthermore, participants will receive up to 8 sessions which involve motivational interviewing and collaborative goal setting to support OSA treatment adherence, and behavioural sleep management. The control arm will not receive OSA treatment as part of this trial, however there will be no OSA treatment restrictions, and any treatment pursued outside the trial will be documented. Primary outcomes are 1) acceptability of the trial participants; 2) alleviating hypoxic burden by reducing OSA severity; 3) tolerability of the outcome assessments. Secondary outcomes include safety and cognitive function. Outcomes will be collected at 0, 6 and 24-months.